2008
DOI: 10.1242/dev.010892
|View full text |Cite
|
Sign up to set email alerts
|

chongmaguereveals an essential role for laminin-mediated boundary formation in chordate convergence and extension movements

Abstract: Although cell intercalation driven by non-canonical Wnt/planar cell polarity (PCP) pathway-dependent mediolateral cell polarity is important for notochord morphogenesis, it is likely that multiple mechanisms shape the notochord as it converges and extends. Here we show that the recessive short-tailed Ciona savignyi mutation chongmague (chm) has a novel defect in the formation of a morphological boundary around the developing notochord. chm notochord cells initiate intercalation normally, but then fail to maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 38 publications
(38 reference statements)
6
121
0
Order By: Relevance
“…To test this, we developed a bioinformatics strategy and applied it to two novel mutant lines, one in C. intestinalis and the other in C. savignyi. The C. intestinalis mutant had a short-tail phenotype ( Figure 1, A and B) closely resembling the chongmague (chm) mutation previously isolated from the related species C. savignyi (Veeman et al 2008) and was named chm-like. A cross-species fertilization test indicated that the C. intestinalis mutant was in the same complementation group as the C. savignyi chm mutant (data not shown).…”
Section: Ciona Mutant Linesmentioning
confidence: 54%
See 1 more Smart Citation
“…To test this, we developed a bioinformatics strategy and applied it to two novel mutant lines, one in C. intestinalis and the other in C. savignyi. The C. intestinalis mutant had a short-tail phenotype ( Figure 1, A and B) closely resembling the chongmague (chm) mutation previously isolated from the related species C. savignyi (Veeman et al 2008) and was named chm-like. A cross-species fertilization test indicated that the C. intestinalis mutant was in the same complementation group as the C. savignyi chm mutant (data not shown).…”
Section: Ciona Mutant Linesmentioning
confidence: 54%
“…Because establishing inbred lines of Ciona has proven to be very difficult, we maintain mutant and transgenic lines by outbreeding them to wild-caught stocks (Veeman et al 2011). Despite this limitation, we have been able to isolate, maintain, and map naturally occurring mutations in C. intestinalis and C. savignyi that disrupt processes such as notochord morphogenesis and neural plate development (Jiang et al 2005;Veeman et al 2008;Tresser et al 2010;Hackley et al 2013). The high level of genetic variation between individuals has actually aided mapping via bulk segregant analysis by providing an abundance of single-nucleotide variation (SNV) markers, although our current mapping procedures are very time consuming.…”
mentioning
confidence: 99%
“…S6D). Recent studies also suggest an important link between PCP signaling and the asymmetric deposition of ECM (23,24). We hypothesized that the disorganized epiblast seen in mpk1 Ϫ/Ϫ mutant reflects a failure in ECM deposition or spindle orientation, on which proper organization of the epiblast, which has the typical characteristics of a pseudostratified epithelium, depends.…”
Section: Ecm Deposition and Orientation Of Mitotic Spindles Are Disrumentioning
confidence: 98%
“…During gastrulation, the net directionality of cell movement is conferred by the stable ''capture'' of rearranging cells at the fibronectin-and lamininrich notochord-somite boundary (reviewed in Wallingford et al, 2002;reviewed in Keller et al, 2008;Veeman et al, 2008). These captured cells then exert traction on neighboring cells, likely facilitated by myosinmediated contractility , to progressively drive convergence toward the axial midline.…”
Section: Gut Morphogenesis Occurs By ''Radially Convergent'' Extensionmentioning
confidence: 99%